Luxury consumers’ behavior: a cross-cultural aspect - Naumova, Olena; Bilan, Svitlana; Naumova, Mariia; Наумова, Олена Олександрівна; Наумова, Олена (LLC CPC Business Perspectives, 2019)
A comprehensive study of the consumers’ needs and demands, the patterns of their social and cultural behavior are essential to the success of the modern luxury companies in their market activity. The purpose of research is to study the possible differences and similarities in the perception of luxury and motivation to purchase these goods by consumers in different parts of the world and selection of acceptable marketing tools. The study is built on the results of analysis of cultural values in some countries using the country comparison tool developed by Hofstede and the results of analysis of scientific articles on the behavior of luxury goods consumers in different countries. The methodology approach – Hofstede’s model of national culture and scientific studies belonging to cultural impacts on luxury consumers’ behavior – is applied to explore cross-cultural differences in luxury consumption behavior. The findings of the study are as follows: consumers from countries with high power distance, collectivism, and masculinity, long-term orientation, and low indulgence primarily perceive social values in consuming luxury goods and are sensitive to conspicuous luxury-status. In cultures with high individualism, masculinity, indulgence, and low power distance, consumers display to perceive individual and functional values and are sensitive to “emotional hedonistic luxury.” The consumption of luxury goods in the Asian region is characterized by significant focusing on social values and status consumption, more than in the rest of the world. The motives of achievements in the form of self-realization and self-actualization are among the main reasons for the luxury consumption of European Union consumers. © The author(s) 2019.
Keywords: consumers’ behavior; luxury market; marketing tools; perception of luxury